Endometriosis encountered in a primigravida and a primipara at caesarean section: Report of two cases - Ojha, Neeva; Kafle, Akinchan; Koirala, Poonam; Shrestha, Isha; Sharma, Savana; Amatya, Sapana; Ghimire, Seeta; Rana, Ashma; Gurung, Geeta (Nepal Journal of Obstetrics and Gynaecology, 2014)
Two cases of posterior uterine surface endometriosis were found at caesarean section in primigarvida and primipara consecutively. These cases are reported to convey the importance of Depo-Provera (depot medroxy progesterone), a three monthly injectable progesterone during the immediate post partum period to avoid the complication that may arise from the surrounding endometriotic deposits during the puerperium and afterwards. DOI: http://dx.doi.org/10.3126/njog.v3i2.10836 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 59-61